Pengaruh Penerapan Blended Learningterhadap Hasil Belajar Mahasiswa Prodi. Pendidikan Biologi FKIP UMS pada Mata Kuliah Komputer Analisis Data - Guntur Nurcahyanto (Universitas Sebelas Maret, 2018)
The purposes of the research were to know the influence of learning between studentstaught using a blended learning model compared to students taught by face to face learning modelof Student’s Achievement in computer of data analysis courses of academic year 2016/2017. This research is a quantitative research of quasi experimental implemented in computer laboratory of FKIP UMS. The study population was all students of the even semester ofbiology education departement of FKIP UMS who take courses computer of data analysis of academic year 2016/2017. The sample of this study was taken 2 classes from 5 classes by choosing cluster random sampling and obtained class G and J with the number of 40 students. Data collection techniques using cognitive tests. The analysis technique used is Kruskal-Wallis H test with softwareSPSS version 20.Research resultswere students who received treatment with the learning model Blended Learning has average cognitive learning outcomes of 91.33 greater than the average of cognitive learning achievement with learning models face to face of 79,73. It can be concluded that the influence of using blended learning and face to face learning modelof student’s achievement in computer of data analysis courses.